1995
DOI: 10.1164/ajrccm.152.5.7582299
|View full text |Cite
|
Sign up to set email alerts
|

Elevated serum hepatocyte growth factor/scatter factor levels in inflammatory lung disease.

Abstract: Hepatocyte growth factor/scatter factor (HGF/SF) plays an important role in tissue repair in liver and renal damage. The clinical significance of this growth factor in these diseases has also been reported. The lung is one of the major sources of HGF/SF; because of this, we investigated serum HGF/SF levels in 26 patients with inflammatory lung disease (15 with interstitial pneumonitis [IP], 11 with bacterial pneumonia [BP]) by enzyme-linked immunosorbent assay. As controls, we measured HGF/SF in the serum of 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
25
1

Year Published

1997
1997
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(27 citation statements)
references
References 14 publications
1
25
1
Order By: Relevance
“…HGF is one of the key factors produced by fibroblasts important in lung pathology (51). In patients with acute lung injury, elevated levels of HGF are found in both serum (52,53) and bronchoalveolar lavage fluid, suggesting its involvement in human lung repair (54). The biological influence of HGF is mediated through its specific receptor, the c-Met tyrosine kinase (55).…”
Section: E Lane 8 Compared With Lane 4)mentioning
confidence: 99%
“…HGF is one of the key factors produced by fibroblasts important in lung pathology (51). In patients with acute lung injury, elevated levels of HGF are found in both serum (52,53) and bronchoalveolar lavage fluid, suggesting its involvement in human lung repair (54). The biological influence of HGF is mediated through its specific receptor, the c-Met tyrosine kinase (55).…”
Section: E Lane 8 Compared With Lane 4)mentioning
confidence: 99%
“…The dashed line was added by the authors. (26), and hepatocyte growth factor/scatter factor (31). At this stage, it is not possible to determine precisely which volatiles are responsible for the sensor response.…”
Section: Discussionmentioning
confidence: 99%
“…HGF reverted to baseline value 6 months after irradiation, concurrent with the disappearance of other symptomatic changes. As serum HGF in patients with lung diseases is reportedly higher [22], HGF is also thought to be one of the inflammation inducing cytokines in human lung. In fact, as HGF production is regulated by multiple factors, we think that these changes do not represent a direct induction of HGF by irradiation, but are the result of indirect and complicated pathways involving radiation lung injury.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, some authors reported that HGF may also play an important role in lung injury and subsequent regeneration, i.e. HGF messenger ribonucleic acid (mRNA) and blood HGF activity were markedly induced and exogeneously and intravenously administered HGF enhanced regeneration of epithelial cells in the trachea after HCl injection [20][21][22].…”
mentioning
confidence: 99%